The Impact of Public Policy on the Promotion and Popularisation of Sports—A Case Study of Healthcare Policy - Zixin Gu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study examines the impact of public policy, specifically health policy, on sports promotion and support. This analysis explores the impact of healthcare policies on sports activities and the significance of public policy in enhancing population health. It evaluates policies across different countries and sectors to determine their effectiveness. The study employs various research methods, including policy analysis, case studies, and secondary data analysis, to offer a comprehensive view of policy effects. The findings indicate that healthcare policies play a vital role in promoting sports. Health insurance, healthcare promotional campaigns, and the construction of appropriate sports facilities all have a significant impact on sports participation levels. Through the implementation of comprehensive sports promotion policies, there was a notable 7.3 percentage point increase observed over a span of five years. The study also emphasises the secondary impacts, such as a slight decrease in healthcare expenses and enhanced approaches to tackling chronic illnesses and mental health concerns. The study highlights the effectiveness of policy interventions, such as the national fitness policy in Nordic countries and South Korea, which emphasise the use of multidisciplinary approaches. Implications: The outcomes provide guidelines for developing and implementing healthcare policies, suggestions for improving long-term Integrated Health Care Policy, and proposals for targeted solutions that address diverse populations.